La situación en Siria de cara al derecho internacional. Una historia de desafíos políticos, jurídicos, y humanos - Reyes Milk, Michelle (2014)
The article focuses on the current situation in Syria in light of international criminal law and international humanitarian law. In particular, the author focuses on events and developments carried out from mid 2013 until September 2014. The author begins her research by providing a brief summary of the reasons that have lead to an armed conflict in Syria, and, inturn, examines the issue of the humanitarian consequences of the conflict, as well as some of the measures that have been adopted by the international community to address such consequences. Some of the main sources for this article are the reports adopted by the Independent International Commission of Inquiry on the Syrian Arab Republic, which provide a crucial tool in order to assess the legal nature and characterization of the armed conflict, particularly in light of the increasing presence of new parties to the conflict. The evolution of the conflict allows the author to further examine the nature of the specific crimes that are being documented in Syria, giving way to an analysis within the field of international criminal law and international criminal responsibility. In the last section, the author examines the role of the UN Security Council in ensuring accountability for crimes in Syria. In particular, the vote on the referral of the Syria situation to the International Criminal Court is thoroughly assessed, leading, in turn, to the current debate on the use of the veto in situations involving crimes under international law.